2021
DOI: 10.1098/rsos.211229
|View full text |Cite
|
Sign up to set email alerts
|

Species identification of Australian marsupials using collagen fingerprinting

Abstract: The study of faunal remains from archaeological sites is often complicated by the presence of large numbers of highly fragmented, morphologically unidentifiable bones. In Australia, this is the combined result of harsh preservation conditions and frequent scavenging by marsupial carnivores. The collagen fingerprinting method known as zooarchaeology by mass spectrometry (ZooMS) offers a means to address these challenges and improve identification rates of fragmented bones. Here, we present novel ZooMS peptide m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…Paleozoological assemblages therefore provide an important window onto the environmental and ecological context of Indigenous economies in both the deep and recent past. In many regions morphological identification of mammalian remains will continue to be necessary where environmental conditions rapidly degrade the DNA or collagen needed for molecular and proteomic identification 69 . Here we have demonstrated that a traditional morphometric approach can classify three macropod pes bones to genus with a high degree of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Paleozoological assemblages therefore provide an important window onto the environmental and ecological context of Indigenous economies in both the deep and recent past. In many regions morphological identification of mammalian remains will continue to be necessary where environmental conditions rapidly degrade the DNA or collagen needed for molecular and proteomic identification 69 . Here we have demonstrated that a traditional morphometric approach can classify three macropod pes bones to genus with a high degree of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Tandem algorithm under the Global Proteome Machine (GPM) user interface software (version 3.0, https://www.thegpm.org/) (Craig and Beavis, 2004, Craig, et al, 2004). Converted mzXML files were searched against the curated SwissProt protein database (downloaded April 2020, 562,895 proteins) supplemented with additional COL1A1 and COL1A2 sequences for species of interest including all available mammalian COL1A1 and COL1A2 sequences from the NCBI protein database, previously reported experimentally-determined marsupial peptide markers (Buckley, et al, 2017, Peters, et al, 2021), and the Common Repository of Adventitious Proteins (cRAP) database (Shin, et al, 2019). Searching was performed with the following specified parameters: Orbitrap instrument method (Âą20 ppm parent ion mass tolerance), fragment ion mass tolerance Âą0.1 Da, trypsin digestion with allowance for two missed cleavages, minimum and maximum peptide sequence lengths of 6 and 50 amino acids, respectively, and up to 4+ charge states allowed.…”
Section: Methodsmentioning
confidence: 99%
“…This technique has been applied to a range of archaeological problems including resolving the evolutionary and phylogenetic history of Darwin’s South American ungulates (Welker, et al, 2015), determining the phylogenetic relationship between a series of extinct giant ground sloths (Buckley, et al, 2015), and distinguishing between mammoth and mastodon fossils (Buckley, et al, 2011). However, very few studies exist in the literature of the application of ZooMS analysis to faunal remains from an Australian context, with none pertaining to relatively recent colonial-era history (Buckley, et al, 2017, Peters, et al, 2021). Here we present the results of the analysis of a collection of six early colonial Australian (c. 1830) bone artefacts excavated from a site in Pyrmont, Sydney, Australia, using a modified ZooMS approach.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, ZooMS has also provided crucial information on human exploitation of marine turtles in several regions ( Harvey et al., 2019b ; Peters et al., 2021 ; Winter et al., 2021 ). Species identification of sea turtles among faunal assemblages is often challenging because of the lack of robust osteomorphological reference material as well as the fragmentary nature of many turtle remains ( Winter et al., 2021 ).…”
Section: Establishing Ecological Baselinesmentioning
confidence: 99%